Respuesta :

Answer:

Step-by-step explanation:

START: 4x + 10 = - 26 ⇔ 4x = - 36 ⇔ x = - 9

[tex]\frac{1}{2}[/tex] x + 13 = 9 ⇔[tex]\frac{1}{2}[/tex] x = - 4 ⇔ x = 8

[tex]\frac{3}{4}[/tex] x - 9 = 27 ⇔ [tex]\frac{3}{4}[/tex] x = 36 ⇔ x = 48

9 - 2x = 35 2x = - 35 + 9 ⇔ x = - 13

[tex]\frac{2}{3}[/tex] x + 15 = 17 ⇔ [tex]\frac{2}{3}[/tex] x = 2 ⇔ x = 3

- 5x - 10 = 10 ⇔ 5x = - 20 ⇔ x = - 4

Now is your turn. You can do it!!!

Ver imagen xenia168

Answer:

Look in the picture;^_^

Start;

[tex]4x + 10 = - 26 \\ 4x = - 26 - 10 \\ 4x = - 36 \\ \\ x = \frac{ - 36}{4} \\ \\ x = - 9[/tex]

To —> – 9

[tex] \frac{1}{2} x + 13 = 9 \\ \\ \frac{1}{2} x = 9 - 13 \\ \\ \frac{1}{2} x = - 4 \\ \\ x = - 4 \div \frac{1}{2} \\ \\ x = - 4 \times 2 \\ x = - 8[/tex]

To —> – 8

[tex] \frac{x}{3} + 10 = 15 \\ \\ \frac{x}{3} = 15 - 10 \\ \\ \frac{x}{3} = 5 \\ \\ x = 5 \times 3 \\ x = 15[/tex]

To —> 15

[tex]9 - 2x = 35 \\ 2x = 9 - 35 \\ 2x = - 26 \\ x = \frac{ - 26}{2} \\ \\ x = - 13[/tex]

To —> – 13

[tex] \frac{2}{3} x + 15 = 17 \\ \\ \frac{2}{3} x = 17 - 15 \\ \frac{2}{3} x = 2 \\ x = 2 \div \frac{2}{3} \\ \\ x = 2 \times \frac{3}{2} \\ \\ x = 3[/tex]

To —> 3

[tex] - 5x - 10 = 10 \\ 5x = - 10 - 10 \\ 5x = - 20 \\ \\ x = \frac{ - 20}{5} \\ \\ x = - 4[/tex]

To —> – 4

[tex] - 8 = \frac{x + 11}{ - 2} \\ \\ x + 11 = - 2 \times - 8 \\ x + 11 = 16 \\ x = 16 - 11 \\ x = 5[/tex]

To —> 5

[tex] - 12x - 17 = - 89 \\ 12x =89 - 17 \\ 12x = 72 \\ x = \frac{72}{12} \\ \\ x = 6[/tex]

To —> 6

[tex]8 - \frac{1}{3} x = 16 \\ \frac{1}{3} x = 8 - 16 \\ \frac{1}{3} x = - 8 \\ x = - 8 \div \frac{1}{3} \\ \\ x = - 8 \times 3 \\ x = - 24[/tex]

To —> – 24

[tex]5 - x = 12 \\ x = 5 - 12 \\ x = - 7[/tex]

To —> – 7

[tex]13 - \frac{3}{2} x = 37 \\ \\ \frac{3}{2}x = 13 - 37 \\ \\ \frac{3}{2} x = - 24 \\ \\ x = - 24 \div \frac{3}{2} \\ \\ x = - 24 \times \frac{2}{3} \\ \\ x = - 16[/tex]

To —> – 16

END! ^_^

I hope I helped you^_^

Ver imagen ghaithgh

Otras preguntas